Audio recording of rock/metal music using personal computers - Laghos, Andrew; Laghos, Panayiotis (My University, 2009)
Personal computers and their relevant technologies have been widely used by artists and musicians to create and record their own music and electroacoustic compositions. “Laptoppers” are famous for using their laptops for their dance/electronic beats and music. A genre that has not relied on the use of PCs for the production of its music is rock/heavy metal, since bands of these genres usually book recording studio time where professionals take on the task of the production using expensive equipment. This study shows that in today’s day and age, and with the software and hardware currently available, it is possible for rock/metal artists to use their PC to record and produce their own CD successfully and at an extremely competitive cost. The effort’s of a rock band that does just this is followed from the beginning and the results of their CD production and song successes is presented. The article also serves as a “HowTo” guide that bands on a low budget can follow to make good quality demo CDs and enter the music business industry.
Keywords: Personal computers; Hardware; Software; Audio; Budget; Music; Production